In Vitro Degradation of PHB/Bacterial Cellulose Biocomposite Scaffolds - Maria Râpă; Cătălin Zaharia; Paul Octavian Stănescu; Angela Cășărică; Ecaterina Matei; Andra Mihaela Predescu; Mircea Cristian Pantilimon; Ruxandra Vidu; Cristian Predescu; Horia Cioflan (International Journal of Polymer Science)
The present work reported the preparation of biocomposites based on poly(3-hydroxybutyrate) (PHB), plasticizer, and bacterial cellulose (BC) by melt processing and their testing by means of thermal properties (DSC), water absorption, and in vitro degradation. The surface of the biocomposites was analyzed via atomic force microscopy (AFM). In vitro degradation of the biocomposites was evaluated by weight loss and thermal properties (DSC) assessment after the immersion of the specimens in phosphate-buffered saline solution (PBS of pH 7.4) over 20 days. The results showed that the BC can reduce the PHB crystallinity and promote its degradation under PBS medium. Moreover, it was found that the water absorption increased as the percentage of BC increased.